التنظيم القانوني للدعوى المباشرة في القانون الأردني - ابومالك, طلال حسين (Gezira Journal of Educational Sciences and Humanities; مجلد 19 عدد 2 (2022), 2023)
تُعد الدعوى المباشرة نظاماً قانونياً مستقلاً يكتسب شرعيته بموجب نص قانوني خاص ومحدد أجاز للدائن صراحة لإقامتها على مدين المدين باسم الدائن ولحسابه الخاص ليستوفي هذا الأخير بواسطتها حقه الثابت بذمة مدينه مباشرة من ذمة مدين مدينه، فيستقل وحده بنتيجتها لما تقضيه قواعد العدالة، أي دون أن يتعرض لمزاحمة دائني مدينه ودون أن يكون الدائن طرفاً في العلاقة العقدية، وباستئثار الدائن بنتائج الدعوى المباشرة التي يقيمها على مدين المدين ويصبح دائن له امتياز على حق مدينه يتقدم على غيره من الدائنين لاستيفاء حقه، وهي خروج على القواعد العامة التي تقضي بأن العقد لا يكون سارياً إلا في حق أطرافه؛ فلا يتعدى أثره إلى الغير لأن الأصل أنّ أثر العقد نسبي من حيث الأشخاص، لا يسري أثره إلا بين من كان طرفاً فيه؛ لهذا عُدّت الدعوى المباشرة استثناءً على مبدأ نسبية العقد، وتُعد نصوصها القانونية من القواعد الآمرة التي لا يجوز مخالفتها أو الاتفاق على ما يخالفها، لذلك تُعد الدعوى المباشرة من النظام العام، ومن الملاحظ بأن النصوص القانونية المقررة للدعوى المباشرة لم تعن ببيان شروط ممارسة تلك الدعوى وبيان الآثار المترتبة عليها؛ مما أدى إلى اختلاف الشُرّاح في تحديد الطبيعة القانونية للدعوى المباشرة، وقيلت في ذلك عدة نظريات فقهية، إلا أنّ أقربها إلى الواقع هي نظرية نص القانون؛  والدعوى المباشرة من النظم القانونية المحددة التي لا ليس لها نظرية عامة لتطبيقها؛ وإنما لابد من صدور نص خاص بها. وكان موقف المشرّع الأردني من الدعوى المباشرة واضحاً بأنه لم يتعرض لهذه الدعوى بنظرية عامة في القانون المدني الأردني؛ حيث عدّها من النظم القانونية المحددة والضيقة، وهذا انعكس على حالاتها وتطبيقاتها في القانون؛ وأهم تطبيقين لها هما: ما جاء في نص المادة (73) من قانون التجارة الأردني، وما جاء في نص المادة (15) من قانون العمل الأردني، أما ما عدا ذلك فهي حالات وتطبيقات محل شك ومنازعة بين شرّاح القانون المدني الأردني. The direct lawsuit is considered as an independent legal system that gains its legitimacy according to a special and specific legal text that expressly authorized the creditor to institute it against the debtor of the debtor in the name of the creditor and for his own account, so that the latter fulfills through it his right established by the debtor directly from the debtor’s debt, so he is independent as a result of what is required by the rules of justice, that is, without He is exposed to competition with the creditors of his debtor without the creditor being a party to the contractual relationship, and with the creditor’s monopoly on the results of the direct lawsuit that he files against the debtor’s debtor, and he becomes a creditor with privilege over the right of his debtor who takes precedence over other creditors to fulfill his right. It is a departure from the general rules that stipulate that the contract is valid only against its parties, so its effect does not extend to others, because the principle is that the effect of the contract is relative in terms of persons, and its effect does not apply except between those who were a party to it. Therefore, the direct lawsuit was considered an exception to the principle of relativity of the contract. . And its legal texts are among the peremptory rules that may not be violated or agreed upon, so the direct lawsuit is considered a matter of public order. It is noted that the legal texts prescribed for the direct lawsuit did not mean the statement of the conditions for the practice of that lawsuit and the statement of the implications of that lawsuit, which led to the difference of commentators in determining the legal nature of the direct lawsuit, and several jurisprudential theories were said, but the closest to reality is the theory of the text of the law. The direct lawsuit is also considered one of the specific legal systems for which there is no general theory for its application, but rather a special text must be issued for it. The position of the Jordanian legislator on the direct lawsuit was clear that he did not address this lawsuit with a general theory in the Jordanian civil law, as he considered it one of the specific and narrow legal systems, and this was reflected in its cases and applications in the law, as the two most important applications for it are what came in the text of Article (73) of the Jordanian Trade Law, and what came in the text of Article (15) of the Jordanian Labor Law.